Application of the drought management guidelines in Greece [Part 2. Examples of application] - Tsakiris G.; Tigkas D.; Vangelis H.; Pangalou D. (Drought management guidelines technical annex, 2007)
The study includes analysis of two watersheds, Nestos and Mornos, selected to represent drought episodes and management in Greece. The study focuses on the methodologies for the drought characterisation and the analysis of the hydrological and agricultural impacts of drought. Furthermore, it analyses the interrelations between the drought indices derived for certain return periods and the impacts on the socioeconomic system and the environment. The operational component reviews the procedures of previous drought events, in order to formulate proposals for successful mitigation actions. Although the Greek organisations have not developed concrete strategies concerning droughts, they have dealt with this phenomenon as a case to case basis, to a certain extent. However, from a review of the existing institutional structure, it can be concluded that the country needs a comprehensive effort to rationalise the entire drought analysis, monitoring and mitigation system. There is an obvious lack of scientific organisations, legal framework and operational capabilities to combat the effects of drought. The new law was approved by the Parliament in November 2003 to comply with the obligation of the member states to harmonise their legal system with the water Direct 2000/60.